2019
DOI: 10.18535/jmscr/v7i3.90
|View full text |Cite
|
Sign up to set email alerts
|

Study of Hyponatremia in Cirrhosis of Liver and It’s Prognostic Value

Abstract: Objective: Study conducted to know the prevalence of hyponatremia in cirrhosis and to evaluate the association between hyponatremia and complications in cirrhosis and its prognostic value. Methods: Patients were selected based on clinical examination, biochemical tests and ultrasound abdomen. All the patients were examined at the time of admission in the hospital and their serum sodium levels were checked and the patients were followed during their stay in the hospital. The severity of cirrhosis was assessed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
1
0
0
Order By: Relevance
“…In the current study, hyponatremic had a statistically significant difference when compared with non-hyponatremic group in the presence of splenomegaly and ascites and high statistically significant difference as regard collaterals. These results were similar to those of Angeli et al, Kim et al, and Maruyama et al, [10,11,14] and as regard ascites and collaterals but was not as regard splenomegaly as Maruyama et al, [9,14] stated no relation between hyponatermia and splenic size, also, Reddy et al, [12] reported significant difference only in refractory ascites. Some authors specify that hyponatremia denotes parenchymal affection and others postulate that it denotes mesenchymal affection with close relation to portal hemodynamics.…”
Section: Discussionsupporting
confidence: 89%
“…In the current study, hyponatremic had a statistically significant difference when compared with non-hyponatremic group in the presence of splenomegaly and ascites and high statistically significant difference as regard collaterals. These results were similar to those of Angeli et al, Kim et al, and Maruyama et al, [10,11,14] and as regard ascites and collaterals but was not as regard splenomegaly as Maruyama et al, [9,14] stated no relation between hyponatermia and splenic size, also, Reddy et al, [12] reported significant difference only in refractory ascites. Some authors specify that hyponatremia denotes parenchymal affection and others postulate that it denotes mesenchymal affection with close relation to portal hemodynamics.…”
Section: Discussionsupporting
confidence: 89%